BUSINESS PROCESS OF RESERVATION, INCOME, AND EXPENSES IN WEBSITE-BASED HOMESTAY: CASE STUDY IN UTAMA HOME - Farel Salsabilla; Ludfi Djajanto; Sumiadji (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This research aims to design a web-based integrated system to optimize the reservation, income, and expense process at Utama Home, a homestay business in Jember. The method used is qualitative with a case study approach, through direct observation and interviews with operational staff. The results of the analysis showed a number of inefficiencies in the manual system, such as overlapping bookings, delay in confirmation, and inconsistent financial records. To overcome these problems, this study uses Business Process Modeling Notation (BPMN) in designing a new system that is able to simplify operational processes, automate transaction recording, and improve real-time data access. The proposed system is designed to improve financial accuracy, accelerate decision-making, and be a sustainable digital transformation strategy for homestay operations. With the implementation of this system, Utama Home is expected to manage business processes more efficiently and professionally, while providing a better service experience for customers.